W stronę wirtualizacji funkcji personalnej w przedsiębiorstwie (zarys procesu) - Antczak, Zbigniew (Virtualization of personnel function in a company (e-HRM), 2006)
The author presents the unique results of research on personnel function in virtual network based companies. Following these changes among other things virtualization of personel function was diagnosed (e-Human Resources Management).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 211-218